2013
DOI: 10.1111/1365-2745.12152
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of tree species sorting along a temperature gradient in New Zealand rain forests: seedling functional traits, growth and shade tolerance

Abstract: Summary 1.It is widely believed that species sorting on environmental gradients reflects trade-offs between competitive ability and physiological tolerance of stresses such as frost and desiccation. One specific expression of this general idea is the hypothesis that tree species sorting on temperature gradients in temperate regions involves a trade-off between growth rate and frost resistance, because adaptations to frost reduce light interception and carbon gain potential. 2. We measured seedling growth of 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 71 publications
(104 reference statements)
1
12
0
Order By: Relevance
“…; Lusk et al. ) and facilitated in others (Michalet et al. ), while relatively stress‐tolerant species may competitively reduce intolerant species in other scenarios (Tilman ; Goldberg & Novoplansky ).…”
Section: Introductionmentioning
confidence: 99%
“…; Lusk et al. ) and facilitated in others (Michalet et al. ), while relatively stress‐tolerant species may competitively reduce intolerant species in other scenarios (Tilman ; Goldberg & Novoplansky ).…”
Section: Introductionmentioning
confidence: 99%
“…Other factors, such as differences in shade tolerance (Standish 2002;Grubb et al 2013), may be playing a role. For example, the lesser shade tolerance of K. excelsa could be a reason for its low seedling survival in the current study, particularly at the three sites where mean canopy openness was below 10%, the suggested threshold at which a species that benefits from canopy openness might be disadvantaged compared with a shade-tolerant species (Lusk et al 2013(Lusk et al , 2015.…”
Section: Discussionmentioning
confidence: 66%
“…While overlapping to a large extent with conifers in their environmental tolerances (Figure 11), and thus co-existing over wide areas, Nothofagaceae are mostly absent from the warmest locations-mainly the north of the North Island and southern North Island lowlands. Like conifers, they are vulnerable to having their regeneration supressed by fastgrowing broadleaves under warm, moist climates but lack the slow-growing emergent strategy that permits conifers to persist in dense broadleaved forests (Lusk et al, 2013). They are also largely absent from the drier, more drought-prone, frostier regions where several tall conifer trees (most notably Podocarpus laetus and Prumnopitys taxifolia) are abundant.…”
Section: Conifers and The Nothofagaceaementioning
confidence: 99%